2017
DOI: 10.32607/20758251-2017-9-1-52-55
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-glycyl-proline (PGP) Peptide Prevents an Increase in Vascular Permeability in Inflammation

Abstract: This study was aimed at investigating the effect of prolyl-glycyl-proline (PGP) tripeptide on vascular permeability in rats with an inflammation. It was found that the peptide reduces the rat paw edema induced by a subcutaneous administration of histamine to the same extent as the conventional anti-inflammatory agent diclofenac. However, an assessment of the relative expression level of the cox-2 gene at the inflammation focus using real-time PCR showed that, in contrast to diclofenac, PGP does not affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Patients were excluded in these conditions: (1) the enrolled patients were lactating women and pregnant women; (2) patients were diagnosed with drugs or food as allergens and with other inducible urticaria; (3) patients had severe immune system diseases of liver, kidney, cardiocerebral vascular, and hematopoietic system and primary diseases; (4) patients systematically used glucocorticoids or immunosuppressive agents; (5) patients had family history of allergies and other systemic allergic diseases. Patients were excluded in these conditions: (1) the enrolled patients were lactating women and pregnant women; (2) patients were diagnosed with drugs or food as allergens and with other inducible urticaria; (3) patients had severe immune system diseases of liver, kidney, cardiocerebral vascular, and hematopoietic system and primary diseases; (4) patients systematically used glucocorticoids or immunosuppressive agents; (5) patients had family history of allergies and other systemic allergic diseases.…”
Section: Subjects and Groupingmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were excluded in these conditions: (1) the enrolled patients were lactating women and pregnant women; (2) patients were diagnosed with drugs or food as allergens and with other inducible urticaria; (3) patients had severe immune system diseases of liver, kidney, cardiocerebral vascular, and hematopoietic system and primary diseases; (4) patients systematically used glucocorticoids or immunosuppressive agents; (5) patients had family history of allergies and other systemic allergic diseases. Patients were excluded in these conditions: (1) the enrolled patients were lactating women and pregnant women; (2) patients were diagnosed with drugs or food as allergens and with other inducible urticaria; (3) patients had severe immune system diseases of liver, kidney, cardiocerebral vascular, and hematopoietic system and primary diseases; (4) patients systematically used glucocorticoids or immunosuppressive agents; (5) patients had family history of allergies and other systemic allergic diseases.…”
Section: Subjects and Groupingmentioning
confidence: 99%
“…Patients were enrolled if they fit in the following items: (1) the course of disease was greater than or equal to 8 weeks; (2) patients were in a stage of disease activity with wheal occurred every day or nearly every day; (3) patients volunteered to carry out autologous serum skin test. Patients were excluded in these conditions: (1) the enrolled patients were lactating women and pregnant women; (2) patients were diagnosed with drugs or food as allergens and with other inducible urticaria; (3) patients had severe immune system diseases of liver, kidney, cardiocerebral vascular, and hematopoietic system and primary diseases; (4) patients systematically used glucocorticoids or immunosuppressive agents; (5) patients had family history of allergies and other systemic allergic diseases. Fourty healthy volunteers, including 19 females and 21 males with the average age of 37 years and without history of allergic diseases were selected as a control.…”
Section: Subjects and Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from proinflammatory activity, numerous beneficial effects of proline-containing short sequences were observed. For example, glyprolines regulate the endothelial permeability 34,35 , hemostasis 36,37 , carbohydrate and lipid metabolism 38 as well as protect gastric mucosa 9 .…”
Section: Biological Activity Of the Collagen-derived Glyprolinesmentioning
confidence: 99%
“…Additionally, the anti inflammatory activity of N‐a‐PGP was displayed by increasing interferon gamma (IFN‐γ) production and improving the antibacterial activity of neutrophils. Bondarenko et al have demonstrated the anti inflammatory properties of glyprolines in the animal model. Their results indicated that PGP prevented the increase of vascular endothelial permeability through the direct effect of the tripeptides on blood vessels and the effect on mastocytes as modulators of vascular permeability.…”
Section: Biological Activity Of the Collagen‐derived Glyprolinesmentioning
confidence: 99%